The challenge of global capitalism : the world economy in the 21st century - Gilpin, Robert; Gilpin, Jean M. (Princeton, NJ : Princeton University Press, 2000)
"The author maintains that global capitalism and economic globalization have rested and must continue to rest on a secure political foundation. However, this foundation has eroded since the end of the Soviet threat. To ensure survival of the global economy, Gilpin concludes, the United States and other major powers must recommit themselves to working together to rebuild its weakened political foundation."--Jacket
List of illustrations -- Acknowledgments -- List of abbreviations -- Introduction: The fragile global economy -- The second great age of capitalism -- The Cold War international economy -- The insecure trading system -- The unstable monetary system -- Global financial vulnerability -- Age of the multinational -- European regional integration -- American economic strategy -- Asian regionalism -- Globalization and its discontents -- Managing the global economy -- Notes -- Selected bibliography -- Index.
Includes bibliographical references (pages 365-370) and index.
Print version record.
JSTOR
Keywords: International economic relations; International relations; Structural adjustment (Economic policy); International trade; Relations économiques internationales; Relations internationales; Ajustement structurel (Économie); Commerce international; international relations; BUSINESS & ECONOMICS -- International -- Economics; BUSINESS & ECONOMICS -- International -- General; International economic relations; International relations; International trade; Structural adjustment (Economic policy); Globalisierung; Weltwirtschaft; Economische politiek; Internationale economische betrekkingen